The Role of Procalcitonin in the Diagnosis and Prognosis of Severe Surgical Patients with Sepsis - Donghua Zheng; Na Liu; Jianhui Ma; Li Chen; Qiang Tai; Guixing Xu (International Journal of Medical Research and Review, 2019)
Purpose:To investigate the clinical significance of serum procalcitonin (PCT) concentrations and related indicators of infection in the early diagnosis and prognosis of severe surgical patients with infection.Methods: This study included 77 critically ill patients taken from the Surgery Department to the Intensive Care unit between June 2015 and July 2017. Patients were divided into control, sepsis and septic shock groups, and their serum concentrations of PCT and related indicators of infection were compared.Results: PCT levels increased significantly from the control to the sepsis group and from the sepsis to the septic shock group (P<0.01 each). There were no significant differences in white blood cell (WBC) count, neutrophil percentage and body temperature among the groups (P>0.05). Receiver operating curve (ROC) analysis showed that the areas under the curve (AUC) for PCT, WBC count, neutrophil percentage and body temperature were 0.949, 0.657, 0.640 and 0.656, respectively. PCT, with 0.52 µg/L as the cut-off concentration, had the highest performance in the diagnosis of severe surgical sepsis, with a sensitivity of 96.1%, a specificity of 92.3% and a Youden index of 0.884.Conclusion: PCT concentration is diagnostic of infection in severe surgical patients, has high specificity in the early diagnosis of sepsis, and can reflect the severity of infection.